The Dynamics of Students' Self-Efficacy in Flipped Classroom-Based Mathematics Instruction - Husnul Asifah; Heni Pujiastuti; Novaliyosi Novaliyosi (International Journal Labs, 2026)
This study examines the dynamics of students’ self-efficacy in flipped classroom-based mathematics instruction and its contribution to improving learning engagement and confidence. The background of this research is rooted in the persistent problem of low student participation, anxiety, and negative perceptions toward mathematics learning, which often affect academic achievement. Therefore, the study aims to explore how the flipped classroom model supports the development of students’ self-efficacy in mathematics learning. This research employed a qualitative literature review approach by analyzing relevant scientific articles related to flipped classrooms, self-efficacy, and mathematics education. Data were collected through documentation techniques and analyzed using thematic analysis to identify patterns regarding the formation and development of self-efficacy. The findings reveal that flipped classroom learning provides meaningful learning experiences through independent study, collaborative discussions, and problem-solving activities. Students become more confident because they are given opportunities to understand the material before classroom interaction and actively participate during learning sessions. Furthermore, the flipped classroom enhances learning independence, critical thinking skills, and emotional readiness while reducing mathematics anxiety. However, the effectiveness of this model is influenced by student readiness, teacher facilitation, and technological support. In conclusion, the flipped classroom is an effective and innovative learning model that can significantly strengthen students’ self-efficacy and improve the quality of mathematics learning in the digital education era.